A Literature Review of Islamic Concepts on Human Rights and Democracy in Indonesia - Mirna Yunita; Kurniati Kurniati; Musyfikah Ilyas (Civiliza Publishing, 2026)
This study aims to examine the concepts of Human Rights and democracy from an Islamic perspective in Indonesia. Human Rights (HR) and democracy have become important topics in social and political life. Democracy is a system of government that involves the active participation of citizens and is closely related to human rights, including equality of rights and obligations. This research focuses on analyzing Islamic concepts of human rights and democracy in Indonesia.This study employs a qualitative descriptive research method. The type of research used is normative research, commonly referred to as library research, which involves collecting data and written works related to human rights and democracy in Indonesia from the perspective of Islamic law.The findings of this study indicate that Islam has a clear and profound understanding of Human Rights and democracy, derived from the teachings of the Qur'an and the Sunnah. Islam affirms that every human being possesses fundamental rights that must be respected, such as the right to life, freedom, justice, and equal treatment. Meanwhile, democracy provides freedom for society while ensuring the protection and recognition of the rights of every individual.